2006
DOI: 10.1177/0310057x0603400406
|View full text |Cite
|
Sign up to set email alerts
|

Sub-Tenon Block: A Learning Curve of 100 Cases

Abstract: This study measures the learning curve for accomplishing sub-Tenon blocks for ophthalmic surgery applicable to anaesthetists skilled in peribulbar techniques. We defined criteria for a good block in terms of chemosis, subconjunctival haemorrhage, globe movement and the need for additional peribulbar block. The overall success rate, by our definitions, was 72% and 56% for the two operators. The overall requirement for an additional peribulbar block was 10%. The rate of additional blocks and reduction in globe m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…In the only study retrieved from a comprehensive literature search, Clarke and colleagues described the sub-Tenon block learning curves of two anesthesiologists experienced in peribulbar anesthesia using the success rates at every 20 blocks in a sequence of 100 blocks performed by each anesthesiologist to assess learning, who stabilized performance after 60 blocks. 11 Thus, to the authors’ best knowledge, this may be the first study describing novice anesthesia residents' peribulbar anesthesia learning curve.…”
Section: Discussionmentioning
confidence: 84%
“…In the only study retrieved from a comprehensive literature search, Clarke and colleagues described the sub-Tenon block learning curves of two anesthesiologists experienced in peribulbar anesthesia using the success rates at every 20 blocks in a sequence of 100 blocks performed by each anesthesiologist to assess learning, who stabilized performance after 60 blocks. 11 Thus, to the authors’ best knowledge, this may be the first study describing novice anesthesia residents' peribulbar anesthesia learning curve.…”
Section: Discussionmentioning
confidence: 84%
“…Therefore care needs to be taken with case selection, consent and degree of supervision until adequate case numbers are achieved. A previous study suggested that improvement in technique continued over the first 60 STB performed 8 .…”
Section: Discussionmentioning
confidence: 99%
“…A posterior sub-Tenon injection of 1% ropivacaine with 15 units/mL of hyaluronidase (mean volume 5 mL) was given for local anaesthesia. 8 All 25G surgical procedures were performed using the Millenium (Baush & Lomb, Rochester, NY, USA) 25G transconjunctival sutureless vitrectomy system. The trocars were placed through the conjunctiva and the sclera by shifting the conjunctiva sidewards.…”
Section: Methodsmentioning
confidence: 99%